Pathogenic PDE12 variants impair mitochondrial RNA processing causing neonatal mitochondrial disease - Lindsey Van Haute; Petra Páleníková; Jia Xin Tang; Pavel A Nash; Mariella T Simon; Angela Pyle; Monika Oláhová; Christopher A Powell; Pedro Rebelo-Guiomar; Alexander Stover; Michael Champion; Charulata Deshpande; et al. (EMBO Molecular Medicine)
Abstract Pathogenic variants in either the mitochondrial or nuclear genomes are associated with a diverse group of human disorders characterized by impaired mitochondrial function. Within this group, an increasing number of families have been identified, where Mendelian genetic disorders implicate defective mitochondrial RNA biology. The PDE12 gene encodes the poly(A)-specific exoribonuclease, involved in the quality control of mitochondrial non-coding RNAs. Here, we report that disease-causing PDE12 variants in three unrelated families are associated with mitochondrial respiratory chain deficiencies and wide-ranging clinical presentations in utero and within the neonatal period, with muscle and brain involvement leading to marked cytochrome c oxidase (COX) deficiency in muscle and severe lactic acidosis. Whole exome sequencing of affected probands revealed novel, segregating bi-allelic missense PDE12 variants affecting conserved residues. Patient-derived primary fibroblasts demonstrate diminished steady-state levels of PDE12 protein, whilst mitochondrial poly(A)-tail RNA sequencing (MPAT-Seq) revealed an accumulation of spuriously polyadenylated mitochondrial RNA, consistent with perturbed function of PDE12 protein. Our data suggest that PDE12 regulates mitochondrial RNA processing and its loss results in neurological and muscular phenotypes.